Pengaruh Earning Per Share (EPS), Net Profit Margin (NPM), Current Ratio (CR) dan Total Assets Turnover (TATO) terhadap Harga Saham Perusahaan Konstruksi yang Tercatat di Bursa Efek Indonesia pada Periode Tahun 2018- 2023 - Azis Thoriqin; Triyono Adi Tristanto (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to examine the influence of Earning Per Share (EPS), Net Profit Margin (NPM), Current Ratio (CR), and Total Asset Turnover (TATO) on the share prices of construction sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018–2023 period. The research method uses a quantitative approach with multiple linear regression analysis, equipped with t-test, F test, and classical assumption test. The research sample amounted to eight companies that were selected using purposive sampling techniques based on the availability and completeness of financial statements. Descriptive analysis shows that several issuers such as ACST, ADHI, WIKA, and WSKT experienced a significant decline in share prices due to the slowdown in infrastructure projects and the Covid-19 pandemic. Meanwhile, DGIK and TOTL tend to be stable, reflecting the resilience of financial performance. The results of the F test show a significance value of 0.001 < 0.05, which means that EPS, NPM, CR, and TATO simultaneously have a significant effect on the stock price. Partially, each variable also showed a significant influence, indicating that profitability, liquidity, and asset efficiency play an important role in the formation of market value. In conclusion, the financial performance reflected in EPS, NPM, CR, and TATO has a strategic role in determining the share price of the construction sector, especially in unstable economic conditions.